Preparation of Ternary-component Sodium Alginate- Low-methyl Pectins-Locust Bean Gum Film and Its Application in Explosion Puffing Drying of Shiitake Mushrooms - Dawei CHANG; Na REN; Jiayi CAO; Huxuan WANG; Yujiao SUN; Wen SHEN; Sendi Sara; Xiaohong ZHI (Shipin gongye ke-ji)
This study focused on the preparation of a ternary composite edible film using sodium alginate (SA), low-methoxyl pectin (LMP), and locust bean gum (LBG) as film-forming materials. The film, termed sodium alginate-low-methoxyl pectin-locust bean gum (SPL), was optimized by adjusting the mass ratio of the components. The rheological properties of the composite film solution were thoroughly analyzed, and critical performance indicators such as mechanical properties (including tensile strength and elongation at break), water vapor permeability coefficient, water solubility, light transmittance, and water contact angle of the film were measured. Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) were utilized to characterize the surface morphology, internal structure, and intermolecular interactions of the composite film. Additionally, this study explored the application effect of SPL ternary composite film coating pretreatment in the explosion puffing drying (EPD) process of shiitake mushrooms. The experimental results indicated that when the mass ratio of SA, LMPs, and LBG was 50:20:30, the prepared SPL ternary composite film exhibited superior comprehensive properties, with a tensile strength of 13.54±0.95 MPa, an elongation at break of 58.15%±4.32%, and a light transmittance of 79.70%±2.31% at a wavelength of 600 nm, demonstrating good mechanical strength and optical properties. The surface of the composite film was smooth, with a uniform and dense internal structure, indicating good interactions and molecular compatibility among SA, LMPs, and LBG. Compared to untreated shiitake mushrooms and those pretreated with only SA film, the quality of EPD shiitake mushrooms pretreated with the SPL ternary composite film, combined with Ca2+ crosslinking, was significantly enhanced.